CONTRIBUTIONS IN ADJUSTMENT OF PSYCHIATES TO EMPLOYEES TO IMPROVE PERFORMANCE - L.N. MIHĂILESCU; L.E. MIHĂILESCU; G. LEOCA (Editura Universitatii Transilvania din Brasov, 2018)
Sports performance is a multifactorial condition and the work emphasizes, in longitudinal experimental research, concrete ways of individualized approach to psychological training in swimming. Fructifying the good practice experiences from the specialized literature, the content of the training, the tools for evaluation and monitoring of the emotional and performance behavior of the subject of the research in the 2017 competition year were elaborated. The results of the research, the performance progress in the contest, validate the methodology of the proposal, research and confirms the working hypothesis.